Diagnostic Challenges and Recovery of First Tarsometatarsal Joint Tuberculosis Extending to Medial Cuneiform and First Metatarsal: A Rare Case Report - Dahal Sweekar; Bist Omkar; Khati Sriram; Bhatta Sunil; Upadhyaya Maya; Pant Shubham (Clinical Case Reports)
ABSTRACT Foot tuberculosis is rare and often diagnosed late due to non‐specific symptoms and lack of typical radiological findings. Early diagnosis and a combination of anti‐tubercular therapy and surgical intervention are crucial for preventing deformities, ensuring successful recovery without significant long‐term complications.